Implementation of National Accounting Standards Focused in Albanian Reality - Xhaferri, Shqipe (Mediterranean Journal of Social Sciences, 2013)
This paper deals with the achievements and weaknesses of the implementation of the National and International Standards ofAccounting, for property in general, the problems encountered in the implementation of these standards as well ascomparisons between different societies.This work will be carried out through questionnaires and direct interviews with variousbusinesses, especially those businesses that deal with the implementation of IAS 16 and 5.The methodology used will bequalitative and quantitative methods and empirical data - where you will get the right information about the problems anddifficulties faced by various companies and qualitative methods through a detailed analysis of the data obtained to reflect thereasons for non-compliance with these standards. Benefits of International Accounting Standards may be financial, economicand political.Preliminary evidence suggests that companies, lenders and investors would prefer, a convergence of domesticaccounting standards with the International Accounting Standards to create a framework of financial reporting quality. Althoughthere are many significant benefits for the implementation of International Accounting Standards and has grown pretty itsimportance, there are still many challenges for the further development and implementation authoritative. To better understandthese challenges need to look at the factors that influence the development of accounting regulations. These factors mayinclude social and cultural values, political and legal systems, business activities and economic conditions; standard-settingprocesses; capital markets and forms of ownership; and finally the cooperative efforts of nations. These factors need to beunderstood if we can mitigate or even eliminate the challenges of International Accounting Standards. International AccountingStandards are important today and will probably become even more important in the future, as they are further developed. Thiswork will be carried out in close cooperation with the theme leader Prof. Jorgji Bolanos to reach the criticism and solutions toproblems encountered in this research.: â€œWhich are the problems that implementation process will face in Albanian reality?â€